2019
DOI: 10.3390/app9040635
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Deformability, Ultrasonic Wave Propagation, and Acoustic Emission of Rock Salt Under Triaxial Compression

Abstract: Ultrasonic waves, which constitute an active testing method, and acoustic emissions (AE), which can be applied as passive testing technology, can reveal rock damage processes in different ways. However, few studies so far have simultaneously adopted both, owing to the limitations of the experimental apparatus. However, the simultaneous use of both methods can improve the experimental efficiency and help to understand the rock damage evolution more comprehensively. In this study, concurrent experiments of ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…For each freezing-thawing cycle, we also observed all the accumulated AE energy of samples had a maximum increasing rate when the counting rate reached the maximum with the formation of through shear crack. is result is consistent with that in other studies such as Li et al [21], who found that the accumulated energy released quickly when rock sample approached to its failure state. e increasing rate of AE energy may be potentially used as an index to identify the big rock fracture.…”
Section: Comparison Of Accumulated Ae Energysupporting
confidence: 93%
See 2 more Smart Citations
“…For each freezing-thawing cycle, we also observed all the accumulated AE energy of samples had a maximum increasing rate when the counting rate reached the maximum with the formation of through shear crack. is result is consistent with that in other studies such as Li et al [21], who found that the accumulated energy released quickly when rock sample approached to its failure state. e increasing rate of AE energy may be potentially used as an index to identify the big rock fracture.…”
Section: Comparison Of Accumulated Ae Energysupporting
confidence: 93%
“…us, the freezing-thawing treatment had a minor influence on the stress-strain behaviors when the confining pressure was still high. is inhibitory effect of confining pressure on crack expansion was also reported by other researchers such as Li et al [21] and Wu et al [33]. e latter research experimentally showed the microcracks partially closed under confining pressure using fluorescence microscopy, but the total porosity was not significantly affected.…”
Section: Stress-strainsupporting
confidence: 71%
See 1 more Smart Citation
“…Paper [8] reports an experimental study of the deformability of media during the propagation of ultrasonic waves and acoustic emission of rock salt at triaxial compression. The study does not consider the propagation of waves in deformable media and their interaction under dynamic mobile loads.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Isah et al [7] introduced a new multichannel fiber Bragg grating sensors (MC-FBGs) to investigate deformation properties of intact rock samples. Li et al [8] studied the deformation and cracking characteristics of rock salt under triaxial compression by ultrasonic waves and AE techniques.…”
Section: Introductionmentioning
confidence: 99%